Feminist Collections, v.9, no.1 (fall 1987) - (:unkn) unknown (My University, 1987)
Subtitle: A Quarterly of Women's Studies Resources. 40p.
FROM THE EDITORS: To encourage scholarship on women of color: national programs and UW System initiatives. FEMINIST PUBLISHING: News of three feminist book fairs and one new press. RESEARCH IN WOMEN'S STUDIES: THE ONLINE CONNECTION: By Ann Pollock. BEYOND STANDARD FORMS OF INFORMATION ORGANIZATION: A WOMAN'S CLASSIFICATION SYSTEM FOR LIBRARIES: By Nancy Humphries. EDITORS' NOTE. NEW REFERENCE WORKS IN WOMEN'S STUDIES: New sources on: women in U.S. religious history; modern Jewish women and their sexuality; current European research in progress; facts about 20th century American women; the black family in the U.S.; British, Irish, Commonwealth, and international feminist periodicals; pay equity research; the Black Women in the Middle West Project; print and nonprint materials on women, war and peace; minority women's health issues and related course syllabi; U.S. women 1987-88. PERIODICAL NOTES: New periodicals on: battered women; feminists fighting pornography; Bay Area news; archives and collections on women in medicine; feminist innovative writing from Canada; H.D.; hysterectomy resources; Iowa women; feminist religious studies; women journalists; a Japanese women's education center; national lesbian issues; women's international news. Special issues on: H.D.; European women in history; women in science: and Buddhist women. Transitions: Media Report to Women has a new publisher; Plexus has reappeared under the same title. Ceased publication: Herizons; M/F. ITEMS OF NOTE: New resources on: primary document reprints; rare and out-of-print books; writings by and about early religious women; AIDS; pamphlets and print-endangered texts from the early women's movement; League of Women Voters papers; child care services at UW; women and the economy; minority women in technology; making women visible in the public school curriculum; dealing with sexist communication; Canadian women's groups; women in health care delivery. BOOK REVIEWS: Women of Central America: Portraying the Reality, by Jean Hopfensperger. Family, Community and Work: Struggles of Asian American Women, by Wendy Ho. BOOKS RECENTLY RECEIVED.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews